2012
DOI: 10.1073/pnas.1200567109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ancient population structure on the degree of polymorphism shared between modern human populations and ancient hominins

Abstract: Recent comparisons between anatomically modern humans and ancient genomes of other hominins have raised the tantalizing, and hotly debated, possibility of hybridization. Although several tests of hybridization have been devised, they all rely on the degree to which different modern populations share genetic polymorphisms with the ancient genomes of other hominins. However, spatial population structure is expected to generate genetic patterns similar to those that might be attributed to hybridization. To invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
149
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(162 citation statements)
references
References 44 publications
9
149
3
1
Order By: Relevance
“…It has been shown that ancient population structure could produce patterns similar to those generated by admixture (48). However, even if this substructure existed in the ancestral population of the AUA and NGH, to suspect that the gene flow we detect here might be an artifact attributable to this substructure would require the age of this ancestry to be much older, predating the colonization of the Sahul (49).…”
Section: Discussionmentioning
confidence: 52%
“…It has been shown that ancient population structure could produce patterns similar to those generated by admixture (48). However, even if this substructure existed in the ancestral population of the AUA and NGH, to suspect that the gene flow we detect here might be an artifact attributable to this substructure would require the age of this ancestry to be much older, predating the colonization of the Sahul (49).…”
Section: Discussionmentioning
confidence: 52%
“…In the recent human lineage, modern humans, Neanderthals, and Denisovans can be considered the daughter lineages of a common parental ancestor. Therefore, expression of shared genetic polymorphisms with Neanderthals and Denisovans in certain extant populations would be the consequence of biogeographical contingency and drift instead of, or in addition to, admixture with other hominins (18,(39)(40)(41). In a similar vein, expression of a plesiomorphic skeletal phenotype in extant and extinct populations has been interpreted as evidence for admixture with, or "assimilation" of, other hominin populations (42).…”
Section: Discussionmentioning
confidence: 96%
“…The paleontological and archaeological records thus far remain elusive. An important consideration, therefore, is the persistence of population substructure in Africa (18,(38)(39)(40)(41), which has been inferred from the human paleontological record (33,34) and is concordant with climate fluctuations in the continent (28,30).…”
Section: Discussionmentioning
confidence: 99%
“…These results were interpreted as evidence of Neanderthals interbreeding with the ancestors of all non-Africans and subsequently a Denisovan-like population mainly with the ancestors of South East Asians [37]; however, marginal Denisovan admixture has also been reported in continental Asian populations [31,38], further entangling this later admixture scenario. This notwithstanding, the proportions of admixture are probably overestimates if some degree of structure was present among ancient humans in Africa, as already pointed out in [28,[39][40][41]. If this were the case, incomplete lineage sorting and not introgression could explain some genetic similarities between modern non-African humans and Neanderthals, although certainly not all of them.…”
Section: The Neanderthal and Denisovan Draft Genomesmentioning
confidence: 92%